2020
DOI: 10.1021/acs.inorgchem.0c00079
|View full text |Cite
|
Sign up to set email alerts
|

Fischer Carbene Complexes of Iridium(I) for Application in Catalytic Transfer Hydrogenation

Abstract: New examples of the very rare class of iridium­(I) Fischer carbene complexes (FCCs) are reported from the facile transmetalation from group 6 FCCs. Postcomplexation modification of either the carbene ligand or the ancillary coligands results in a tunable IrI metal center, for unprecedented application as a (pre)­catalyst in a benchmark transfer hydrogenation reaction. The introduction of an aminocarbene ligand with a pendant N-donor moiety capable of hemilabile coordination yielded the best catalytic results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…To fully understand the effect of the base in the TH of ketones, we carried out a number of control experiments. First, an experiment using KOH base alone without the ruthenium complex was conducted and afforded percentage conversions of 5% (6 h) and 16% within 36 h (Table 2, entries 1 and 2) and are consistent with the findings reported by Polshettiwar et al 43,44 This is much lower compared to the percentage conversions of 86% (6 h) reported using the Ru3/ KOH system (Table 2, entry 9), thus confirming that the catalytic activities observed are due to the Ru( ii ) carboxamide complexes. In another control experiment, we used complexes Ru3 and Ru4 without adding any base.…”
Section: Resultssupporting
confidence: 86%
“…To fully understand the effect of the base in the TH of ketones, we carried out a number of control experiments. First, an experiment using KOH base alone without the ruthenium complex was conducted and afforded percentage conversions of 5% (6 h) and 16% within 36 h (Table 2, entries 1 and 2) and are consistent with the findings reported by Polshettiwar et al 43,44 This is much lower compared to the percentage conversions of 86% (6 h) reported using the Ru3/ KOH system (Table 2, entry 9), thus confirming that the catalytic activities observed are due to the Ru( ii ) carboxamide complexes. In another control experiment, we used complexes Ru3 and Ru4 without adding any base.…”
Section: Resultssupporting
confidence: 86%
“…While traditional methods such as direct hydrogenation or transfer hydrogenation have been intensively explored in this area, these methods still have some major draw backs, as the need for precious metal catalysts, , complicated (chemo-)­selectivity strategies, or the need for pressurized reactors, which are not commonly available in all laboratories, as well as the need for potentially hazardous hydrogen gas . Although the latter can be overcome by using transfer hydrogenation processes , with different hydrogen delivering reagents, e.g., isopropanol or silanes, these protocols often require a large excess of hydrogen suppliers and may create large amounts of (hazardous) waste byproducts. , In this context, oxygen atom transfer reactions (OATR, Scheme )­ hold great promise, not only because of their high atom efficiency but also due to simple executions and the need for cheap, earth-abundant early transition metals. Furthermore, OAT reactions focus only on oxygen containing functional groups, which makes them ideal candidates for chemoselective reductions compared to “classical” hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Highly active catalytic transfer hydrogenation of acetophenone using the Ir( i ) acyclic carbene complexes has also been reported. 103 Their catalytic performances in terms of product yield and TOF with 0.1 mol% catalytic loading are superior to those of related complexes with cyclic carbene ligands.…”
Section: Catalystsmentioning
confidence: 99%
“…18) have also been reported to catalyze addition reactions of aldehydes and ketones (Scheme 6). 102,103 A series of Rh(I) acyclic carbene complexes can efficiently catalyze the addition of aryl boronic acids to benzaldehydes with an yield up to 96%. 102 The enantioselectivity of the catalysis can be improved by modification of the substituents of the carbene ligands (Table S4, ESI †).…”
Section: Addition Reactionsmentioning
confidence: 99%